UDCA Inhibits Hypoxic Hepatocellular Carcinoma Cell-Induced Angiogenesis Through Suppressing HIF-1α/VEGF/IL-8 Intercellular Signaling - Wanfu Lin; Wanfu Lin; Shu Li; Yongbin Meng; Guokai Huang; Shufang Liang; Juan Du; Juan Du; Qun Liu; Binbin Cheng; Binbin Cheng (Frontiers Media S.A., 2021)
Background: A hypoxic microenvironment may induce angiogenesis and promote the development of hepatocellular carcinoma (HCC). The aim of this study was to evaluate whether ursodeoxycholic acid (UDCA) may inhibit hypoxic HCC cell-induced angiogenesis and the possible mechanisms.Methods: Tube formation and matrigel plug angiogenesis assays were used to evaluate angiogenesis in vitro and in vivo, respectively. Real-time PCR, enzyme-linked immunosorbent assay, and Western blot were used to evaluate the mRNA and protein expressions of hypoxia-inducible factor-1α (HIF-1α), vascular endothelial growth factor (VEGF), and IL-8, respectively. Dual-luciferase reporter assay was applied to assess the reporter gene expression of hypoxia-response element (HRE).Results: UDCA antagonized hypoxic Huh 7 cell-induced tube formation of EA.hy 926 cells. In HCC cells, UDCA inhibited hypoxia-induced upregulation of VEGF and IL-8 both in mRNA and protein levels. UDCA also inhibited IL-8-induced angiogenesis in vitro and in vivo through suppressing IL-8-induced phosphorylation of ERK. The levels of HIF-1α mRNA and protein and HRE-driven luciferase activity in HCC cells were upregulated by hypoxia and were all inhibited by UDCA. The proteasome inhibitor MG132 antagonized the effect of UDCA on HIF-1α degradation. In hypoxic condition, the phosphorylation of ERK and AKT was obviously increased in HCC cells, which was suppressed by UDCA. Transfection of the HIF-1α overexpression plasmid reversed the effects of UDCA on hypoxic HCC cell-induced angiogenesis, HRE activity, and expressions of IL-8 and VEGF.Conclusions: Our results demonstrated that UDCA could inhibit hypoxic HCC cell-induced angiogenesis through suppressing HIF-1α/VEGF/IL-8-mediated intercellular signaling between HCC cells and endothelial cells.